Markaların Kişilik Arketiplerinin Algılanması Üzerine Bir Araştırma - Yakın, Volkan; Ay, İfakat Canan (The Turkish Online Journal of Design Art and Communication, 2012)
It is a well known reality that strong brands hold strong personalities. Therefore, building up a brand personality became an issue of increasing importance in branding efforts - especially in today's digital age. This paper investigates the perception of brand personality through personality archetypes, which is related to Jung’s collective unconscious and archetype theory. For this purpose, an online research was conducted with one hundred college students. To begin with, the students were informed about the meaning of the twelve personality archetypes at the online research site. After this introduction, various print advertisements were presented and the students were asked to indicate which archetypes they perceive in each print. The results show that different product categories are reflected and represented by the different archetypes. It is also noted that men and women have different archetype perceptions for some of the prints.
Keywords: Brand Personality; Archetype; Archetypal Brand Personality; Marka Kişiliği; Prototip; Arketip Marka Kişiliği